Նարեկեան մի քանի պատկերներու Փիլոնեան նախապատկերները - Տէրեան, Աբրահամ («Նաիրի» հրատ.)
The Philonic influence on St. Gregory of Narek is both direct and indirect. The direct influence comes from having nearly half of the Philonic corpus translated into Armenian in the sixth century, which includes works extant in Armenian only. The indirect influence is associated with the inevitable impact of Greek patristic writings translated into Armenian as of the fifth century, especially of works by the Cappadocian Fathers who were themselves influenced by Clement of Alexandria and Origen, the transmitters of the Philonic tradition of allegorical reading of the Bible. Illustrative of this influence, some ten examples are given which also help illumine hard-to-understand images in the festal works of St. Gregory of Narek: his odes, litanies, and encomia, to which these examples are limited. The allegorized images here considered include the Logos as the Image and Breath of God in humans, the dew as divine descent with implications for incarnational Christology, Trinitarian formulae, Ecclesiological / cosmological images, even mundane images of insects and the fat of sacrifices. Gregory broadens the significance of these allegorized images with perspectives of his own. Влияние Филона на Григора Нарекаци двоякое – прямое и опосредованное. Прямое влияние определяется переведенной в шес-том веке на армянский язык почти половиной филоновского кор-пуса, включающего также произведения, сохранившиеся только на армянском. Опосредованное Опосредованное влияние связано с неизбежным воз-действием трудов греческой Патристики, которые переводились на армянский начиная с пятого века, в особенности – произведений Каппадокийских отцов, в свою очередь подвергшихся влиянию Кли-мента Александрийского и Оригена, передатчиков филоновской традиции комментирования Библии. В статье это влияние иллю-стрируется на десяти примерах, в частности способствующих прояснению трудных для понимания образов в праздничных сочине-ниях св. Григора Нарекаци – его одах, литаниях и панегириках, кото-рыми ограничиваются эти примеры. Рассмотренные здесь аллегори-ческие образы включают Логос как образ и как Вдыхание Богом жизни в человека, росу как божественное нисхождение, с отнесением его к христологии воплощения, формулы, касающиеся Троицы, экклесиологические / космологические образы, даже мирские обра-зы насекомых и жира жертвенных животных. У Григора собствен-ное, более широкое видение значения этих аллегорических образов.
Keywords: Գրիգոր Նարեկացի; Մեկնողական գրականություն